Process control in next-generation sewing machines : a project overview - Carvalho, Helder (2003)
The sewing machine created in the XIX century has roughly remained unchanged in its basic technologies. Although a great range of mechanical and electronic technologies has boosted its development enormously, the process of sewing itself, however, although perfected in many aspects, has remained uncontrolled.Many of the phenomena occurring at high-speed sewing (up to 10000 stitches per minute) are still not properly understood. This project is creating a deeper insight into the sewing process, identifying and describing the variables that can be monitored and/or controlled in a way that ensures a better control of this production process. Some monitoring and control algorithms are already under test. Concurrently the project develops software support tools to allow the up-front engineering of the process, resulting in control parameters to be downloaded to the machine controllers. The software would also serve as a support tool for the textile manufacturer, to tune and improve materials’ properties and define the relationship between materials and optimum sewing conditions.